PENGARUH KREDIBILITAS PERSONAL BRAND @SHIREEENZ TERHADAP NIAT BELI KONSUMEN MELALUI EKUITAS MEREK ISTREYA - Sarah Sofia Sudjatnika; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The “Founder-as-Influencer” phenomenon in Indonesia’s modest fashion industry positions the credibility of brand founders as the spearhead communication. of digital Shirin Al marketing Athrus (@shireeenz) and the hijab brand Istreya provide a relevant context for testing whether personal brand credibility truly drives consumer purchase intent or requires a specific mediator for that influence to materialize. This study aims to explain the influence of @shireeenz’s personal brand credibility on consumer purchase intent, with Istreya’s brand equity serving as a mediating variable, based on Source Credibility Theory and the Customer-Based Brand Equity Model. This study employs an explanatory quantitative approach targeting Muslim women who meet the research criteria, with mediation The research findings show that the credibility of the @shireeenz personal brand—which encompasses the dimensions of trustworthiness, expertise, and attractiveness—is rated very highly by the majority of respondents. However, this credibility was not found to have a significant direct influence on consumers’ purchase intent, indicating that consumers do not automatically form a desire to buy based solely on their perception of the figure promoting the product. Conversely, Istreya’s brand equity was found to significantly mediate the relationship between the credibility of @shireeenz’s personal brand and analysis conducted using PROCESS Macro Model 4 and a bootstrap confidence interval approach. consumer purchase intent. This mediation is full, meaning that the influence of personal brand credibility can only take effect if it first builds strong brand equity through brand awareness, perceived quality, brand associations, and brand loyalty. Thus, it is concluded that the popularity and credibility of a founder-influencer’s personal brand are not sufficient to directly drive consumer purchase intent without the support of strong brand equity. Therefore, Istreya is advised to consistently optimize brand equity building by strengthening brand awareness, improving perceptions of product quality, creating positive brand associations, and maintaining long-term customer loyalty.